Transforming Education Summit 2022: Barbados Consultation Report - Barbados. Ministry of Education (My University, 2022)
The Barbados Consultation Report noted that Barbados is currently implementing an education reform agenda, which is located in the context of numerous issues existing in the sector. These issues include but are not limited to persistent under-performance; student disengagement and indiscipline; programming out of sync with the needs of the economy; weak leadership and instructional quality; the absence of standards and accountability; and an archaic regulatory framework. Some major points identified for further discussion across the thematic tracks were inclusive, equitable, safe and healthy schools, learning and skills for life and sustainable development, teachers, teaching and the teaching profession, digital learning and transformation, and financing of education.
Transforming Education Summit United Nations, New York, 16, 17 & 19 September 2022